Acute caloric restriction counteracts hepatic bile acid and cholesterol deficiency in morbid obesity. (6th March 2017) - Straniero, S.; Rosqvist, F.; Edholm, D.; Ahlström, H.; Kullberg, J.; Sundbom, M.; Risérus, U.; Rudling, M.
Abstract: Background: Bile acid (BA) synthesis is regulated by BA signalling in the liver and by fibroblast growth factor 19 (FGF19), synthesized and released from the intestine. In morbid obesity, faecal excretion and hepatic synthesis of BAs and cholesterol are strongly induced and caloric restriction reduces their faecal excretion considerably. We hypothesized that the high intestinal food mass in morbidly obese subjects promotes faecal excretion of BAs and cholesterol, thereby creating a shortage of both BAs and cholesterol in the liver. Methods: Ten morbidly obese women (BMI 42 ± 2.6 kg m −2 ) were monitored on days 0, 3, 7, 14 and 28 after beginning a low‐calorie diet (800–1100 kcal day −1 ). Serum was collected and liver size and fat content determined. Synthesis of BAs and cholesterol was evaluated from serum markers, and the serum levels of lipoproteins, BAs, proprotein convertase subtilisin/kexin type 9 (PCSK9), insulin, glucose and FGF19 were monitored. Fifty‐four nonobese women (BMI <25 kg m −2 ) served as controls. Results: At baseline, synthesis of both BAs and cholesterol and serum levels of BAs and PCSK9 were elevated in the obese group compared to controls. Already after 3 days on a low‐calorie diet, BA and cholesterol synthesis and serum BA and PCSK9 levels normalized, whereas LDL cholesterol increased. FGF19 and triglyceride levels were unchanged, and liver volume was reduced by 10%. Conclusions: The results suggest that hepatic BAs and cholesterol are deficient in morbid obesity. Caloric restriction rapidly counteracts these deficiencies, normalizing BA and cholesterol synthesis and circulating PCSK9 levels, indicating that overproduction of cholesterol in enlarged peripheral tissues cannot explain this phenotype. We propose that excessive food intake promotes faecal loss of BAs and cholesterol contributing to their hepatic deficiencies.